1996
DOI: 10.1111/j.1471-0307.1996.tb02498.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality assurance of edible table spreads in new product development

Abstract: The microbiological quality assurance (MQA) of edible table spreads, including milk fat, margarine type and blended products having fat contents in the range 5–80% by weight, in new product development is considered in relation to the sampling and monitoring of marker microorganisms, hazard and risk analyses, challenge testing, preservative efficacy testing and the modelling of the growth of spoilage micro‐organisms in compartmentalized food emulsion systems. It is shown that the use of ingredient and process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…The density of the cells at the stationary phase also decreased as the hexadecane concentration increased. This phenomenon is in agreement with other studies (Brocklehurst and others 1993;Brocklehurst 1995a;Charteris 1995;Charteris 1996). The increase in generation time of bacteria in the emulsions may be due to growth under several limitations.…”
Section: Growth Of Bacteria In 0% 5% 20% and 40% Hexadecane In Stasupporting
confidence: 93%
“…The density of the cells at the stationary phase also decreased as the hexadecane concentration increased. This phenomenon is in agreement with other studies (Brocklehurst and others 1993;Brocklehurst 1995a;Charteris 1995;Charteris 1996). The increase in generation time of bacteria in the emulsions may be due to growth under several limitations.…”
Section: Growth Of Bacteria In 0% 5% 20% and 40% Hexadecane In Stasupporting
confidence: 93%
“…Ibrahim et al (1994) and Reddy et al (2001) reported noticeable increases in TVC of LFS. Similarly, Charteris (1996) also reported significant increase in the standard plate count due to wide usage of dairy ingredients such as skim milk, buttermilk and SMP etc. in the formulation of table spread.…”
Section: Resultsmentioning
confidence: 89%
“…A reduced agitation rate on the second A‐C unit was used to alter (or control) the dispersed moisture droplet size distribution in the biospread. Increasing the number of moisture droplets with a diameter > 30 µm will increase the viability of both the indigenous 74 and exogenous micro‐organisms of the aqueous phase (this study), since for nutrient‐dense emulsions such as those comprising milk proteins, microbial viability and growth is limited primarily by the available space within moisture droplets 65 …”
Section: Discussionmentioning
confidence: 99%
“…Increasing the number of moisture droplets with a diameter > 30 µm will increase the viability of both the indigenous 74 and exogenous micro-organisms of the aqueous phase (this study), since for nutrientdense emulsions such as those comprising milk proteins, microbial viability and growth is limited primarily by the available space within moisture droplets. 65 Nitrogen (OFN) addition (by means of sparging, blanketing and in-line injection) is an effective means of continually protecting lipids through to packaging. Peroxide development and flavour instability can be virtually eliminated by minimizing oxygen levels in contact with and dispersed within the product.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation